Health Education to Increase Nutrition Awareness in the Elderly in Karangduren Village, Malang Regency - Asruria Sani Fajria; Nurya Viandika; Leliana M De Conceicao; Lucia Claritha Leki; Ermalinda Lalian; Setlin (Journal of Community Engagement in Health, 2025)
Elderly is the final stage of the human life cycle, which at this stage experiences many changes both physically and mentally, especially decline in various functions and abilities that were once possessed. Health factors that play a role in changes in nutritional status include the increasing incidence of degenerative and non-degenerative diseases that result in changes in food intake, changes in the absorption of nutrients at the tissue level, and some cases can be caused by certain drugs that must be minimized by the elderly due to the disease they are suffering from. Fulfillment of good nutritional needs needs to be supported by knowledge of nutrition itself so that it can provide complete benefits for the elderly. After health counseling is carried out, it is hoped that it can improve the health degree and quality of elderly services as a process of early detection and health improvement. This activity will be carried out in August 2024. The implementation method is carried out by lectures and discussions. The media used are nutritional leaflets on the elderly, LCDs, laptops and projectors. The implementation of health counseling is carried out by bringing the elderly to the counseling site and providing a pre-test before being given health education and a post-test after being given health education. The result of this activity is an increase in the level of knowledge of 100% of the elderly about nutrition in the elderly. This activity concluded that under this activity it was carried out and produced changes in accordance with the output target, namely knowledge about nutritional fulfillment in the elderly. It is hoped that the counseling provided can be implemented and applied to daily life.